Inter-Religious Engagement Fight For Environmental Crisis: Eco-Bhinneka Muhammadiyah as a Facilitator of Religious Harmony through Environmental Care - Musdodi Manalu (Religi: Jurnal Studi Agama-agama, 2023)
This research explores the role of Eco-Bhineka Muhammadiyah Indonesia in building interfaith harmony through environmental awareness. Eco-Bhineka Muhammadiyah is a community-based movement that promotes environmental conservation and interfaith cooperation. Using qualitative methods, this study explores the motives and experiences of Eco-Bhineka Muhammadiyah members in interacting with other religious communities. The research findings show that the movement has successfully fostered interfaith harmony and collaboration through various activities, such as waste management, promoting environmentally friendly lifestyles, and interfaith dialogue. Eco-Bhineka Muhammadiyah has also helped break down stereotypes and prejudices among members of different religious communities and promote a shared commitment to environmental protection. This study contributes to understanding how environmental initiatives can serve as a platform for interfaith dialogue and cooperation and how such initiatives can contribute to building a more inclusive and harmonious society.